The Role of the General Election Supervisory Agency (Bawaslu) in Handling Vote Shifts in the 2024 General Elections - Niode, Burhan; Wullur, Magdalena; Pengemanan, Johnly; Piter, Yukbel (Dinasti Research, 2025)
This study aims to examine the role of the General Election Supervisory Agency (Bawaslu) of North Minahasa Regency in handling cases of vote shifting in the 2024 election in West Likupang District, North Minahasa Regency. The method used in this study is a qualitative method. Data was obtained through interviews and document analysis in the context of tracing the supervision, prevention, and enforcement functions by the Bawaslu of North Minahasa Regency. The results of the study show that the Bawaslu of North Minahasa Regency actively coordinates with the General Election Supervisory Committee (Panwaslu) of West Likupang District and the Integrated Law Enforcement Center (Gakkumdu) to maintain the integrity of the election, but faces obstacles in the form of limited resources, low community participation in supervision activities. Based on the institutional theory of W. Richard Scott, this study found that the regulatory pillars are effective, while the normative and cognitive aspects of culture need to be strengthened to increase transparency and fairness. This study recommends increasing public political awareness in supervision and collaboration between institutions related to community participatory strengthening activities and preventing election violations in order to create credible and integrity elections.